2004
DOI: 10.2140/pjm.2004.215.3
|View full text |Cite
|
Sign up to set email alerts
|

Some properties of the probabilistic zeta function of finite simple groups

Abstract: In the factorial ring of Dirichlet polynomials we explore the connections between how the Dirichlet polynomial P G (s) associated with a finite group G factorizes and the structure of G. If P G (s) is irreducible, then G/Frat G is simple. We investigate whether the converse is true, studying the factorization in the case of some simple groups. For any prime p ≥ 5 we show that if P G (s) = P Alt(p) (s), then G/Frat G ∼ = Alt(p) and P Alt(p) (s) is irreducible. Moreover, if P G (s) = P PSL(2,p) (s), then G/Frat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 8 publications
0
19
0
Order By: Relevance
“…The ring R of Dirichlet polynomials is a factorial domain and an important role in the factorization of P G (s) in R is played by the normal subgroups of G. We recall a result in this direction that has been employed already in [4] …”
Section: The Main Theoremmentioning
confidence: 99%
See 2 more Smart Citations
“…The ring R of Dirichlet polynomials is a factorial domain and an important role in the factorization of P G (s) in R is played by the normal subgroups of G. We recall a result in this direction that has been employed already in [4] …”
Section: The Main Theoremmentioning
confidence: 99%
“…In [4] we showed that if n is a prime number, then P Alt(n) (s) is irreducible and G/ Frat G Alt(n). Hence we shall assume that n is not a prime number.…”
Section: The Main Theoremmentioning
confidence: 99%
See 1 more Smart Citation
“…The above theorem was proved for G ∼ = A 1 (p), p prime, in [7] and for G ∼ = A 1 (t), 2 B 2 (t 2 ) and 2 G 2 (t 2 ) in [25]. Now, we turn to a more general setting.…”
Section: Introductionmentioning
confidence: 91%
“…Classical groups, class S S π S (S) (l, t) A l (t) t l+1 , t l (2, 4), (5, t), (7,2), (17,3), (19,2) and (3, 2 k …”
mentioning
confidence: 99%